(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the concept of random events, their main types, their role in probability theory, and their applications in modern science and technology. The classification of random events, methods of calculating probabilities, and their importance in modeling real-life processes are discussed. In addition, the practical applications of probability theory in economi